2011
DOI: 10.3109/14767058.2011.561895
|View full text |Cite
|
Sign up to set email alerts
|

Ionized calcium levels in umbilical cord blood of women with preeclampsia and normotensive pregnancies

Abstract: Calcium is essential for normal fetal growth and development. During intrauterine life, the fetus is entirely dependent on the mother and a normally functioning placenta for calcium accretion. Preeclampsia is associated with abnormal calcium metabolism and placental dysfunction. The objective of our study was to investigate ionized calcium levels in the umbilical cord arterial blood of women with preeclampsia and normotensive pregnancies. There were 24 women in the preeclampsia group and 25 in the normotensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that decreased endothelial progenitor cells and ionized calcium levels were found in umbilical cord blood in preeclampsia [12,13]. There were significant differences in nucleated red blood cell count and blood rheological properties in the umbilical cord blood between healthy women and women with preeclampsia [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that decreased endothelial progenitor cells and ionized calcium levels were found in umbilical cord blood in preeclampsia [12,13]. There were significant differences in nucleated red blood cell count and blood rheological properties in the umbilical cord blood between healthy women and women with preeclampsia [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…More and more studies have shown that exosomal circrnas are involved in the processes of cell growth, angiogenesis, epithelial mesenchymal transition and targeted therapy [16,17]. And accumulating evidences suggested that it is possible to identify functional and/or structural differences in umbilical cord blood with risk of PE [18][19][20]. Therefore, we speculated that exosomal circRNA in umbilical cord blood might play an important role in the regulation of PE development as a new placental derived factor.…”
Section: Introductionmentioning
confidence: 95%
“…More and more studies have shown that exosomal circRNAs are involved in the processes of cell growth, angiogenesis, epithelial mesenchymal transition and targeted therapy [ 16 , 17 ]. And accumulating evidences suggested that it is possible to identify functional and/or structural differences in umbilical cord blood with risk of PE [ 18 20 ]. Therefore, we speculated that exosomal circRNA in umbilical cord blood might play an important role in the regulation of PE development as a new placental derived factor.…”
Section: Introductionmentioning
confidence: 99%